2017
DOI: 10.1158/1078-0432.ccr-17-0001
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of Human Endogenous Retrovirus Type K (HERV-K) Viral env RNA in Pancreatic Cancer Cells Decreases Cell Proliferation and Tumor Growth

Abstract: Purpose We investigated the role of the human endogenous retrovirus type K (HERV-K) envelope (env) gene in pancreatic cancer (PC). Experimental Design shRNA was employed to knockdown (KD) the expression of HERV-K in PC cells. Results HERV-K env expression was detected in seven PC cell lines and in 80% of PC patient biopsies, but not in two normal pancreatic cell lines or uninvolved normal tissues. A new HERV-K splice variant was discovered in several PC cell lines. RT activity and virus-like particles were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 67 publications
(85 reference statements)
5
94
0
Order By: Relevance
“…We focused on HERV-K because, of the dozens of HERV families, only HERV-W and HERV-K were repeatedly reported to have potentially pathogenic properties, both linked to the proteins coded by their env genes. The HERV-W is linked to multiple sclerosis [ 49 , 50 ], and the HERV-K to cancer [ 5 , 51 ] and amyotrophic lateral sclerosis [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on HERV-K because, of the dozens of HERV families, only HERV-W and HERV-K were repeatedly reported to have potentially pathogenic properties, both linked to the proteins coded by their env genes. The HERV-W is linked to multiple sclerosis [ 49 , 50 ], and the HERV-K to cancer [ 5 , 51 ] and amyotrophic lateral sclerosis [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, increased HERV-K expression in tumors is associated with shorter relapse-free survival [ 58 ]. The HERV-K Env protein was shown to promote key signaling pathways, involved in cellular movements, cancer, cell death/survival, and cell proliferation, with a central role in regulating the RAS-ERK-RSK signaling pathway [ 39 , 52 ]. After HERV-K knockdown, breast cancer cells undergo a reversion to a non-tumorigenic phenotype, with a major downregulation of EGF-R and NF-κB [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated HERV‐K gag expression in PBMC was associated with prostate cancer diagnosis particularly in older men and smokers who tend to develop a more aggressive disease . Recently, HERV‐K env expression was detected in pancreatic cancer cell lines and in 80% of pancreatic cancer patient biopsies, but not in normal pancreatic cell lines or uninvolved normal tissues . The significantly elevated expression of numerous HERV elements in various cancers has accelerated their use as biomarkers for cancer aggressiveness and malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different families, retroviral sequences of the HERV-K family (HML-2) were the latest acquired, therefore they are the most complete and biologically active family ( Bannert and Kurth, 2004 ; Hughes and Coffin, 2004 , 2005 ). HERV-K expression was detected in several tumor entities, among them chronic myeloid leukemia ( Brodsky et al, 1993 ), renal cell carcinoma ( Florl et al, 1999 ; Kreimer et al, 2013 ), breast carcinoma ( Wang-Johanning et al, 2003 ), prostate carcinoma ( Wallace et al, 2014 ), pancreatic cancer ( Li et al, 2017 ), and melanoma ( Serafino et al, 2009 ). In melanoma, HERV-K expression is suggested to be an early event in tumorigenesis, seemingly enhancing the pathological process of tumor formation ( Serafino et al, 2009 ; Cegolon et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma, HERV-K expression is suggested to be an early event in tumorigenesis, seemingly enhancing the pathological process of tumor formation ( Serafino et al, 2009 ; Cegolon et al, 2013 ). Most recently, it was demonstrated that shRNA-mediated downregulation of HERV-K in pancreatic cancer cell lines suppressed growth rates and metastases as well as the expression of several proliferation-related genes ( Li et al, 2017 ). However, it is worth mentioning that the above described associations between HERV expression and tumor tissues are correlative.…”
Section: Introductionmentioning
confidence: 99%